Pemenuhan Hak Pengurangan Masa Pidana (Remisi) Terhadap Narapidana di Lembaga Pemasyarakatan - Marwati Marwati; Suardi Suardi; Moch. Alafatah Alti Putra (Jurnal Litigasi Amsir, 2024)
The aim of this research is to determine the fulfillment of the right to reduce the sentence period (remission) for prisoners at the Parepare Class IIA Correctional Institution. To find out the factors that hinder the implementation of the right to reduce the sentence (remission) for prisoners at the Parepare Class IIA Correctional Institution. The research method was carried out using empirical juridical research. The research results show that the fulfillment of the right to reduce the criminal period (remission) in the Class IIA Parepare correctional institution has implemented the granting of remissions to prisoners in accordance with existing laws and regulations. The factors inhibiting the implementation of the right to reduce the criminal period (remission) for prisoners in the Parepare Class IIA Correctional Institution are juridical factors, institutional and human resource factors, facilities and infrastructure factors, factors of prisoner behavior, and cultural factors. Another factor is external factors, namely obstacles to remission that occur outside the prisoner himself, and outside the authority of the Class II A Parepare Penitentiary.